Delayed neuroprotection against cerebral ischemia reperfusion injury: putative role of BDNF and GSK-3β. (3rd July 2016) - Taliyan, Rajeev; Ramagiri, Sruthi
Abstract: Aim : Numerous studies have demonstrated the possible neuroprotective role of lithium treatment against neurological disorders. However, the role of lithium in delayed phase of neuronal death against focal ischemia has not been explored. Therefore, the present study was designed to investigate the effect and molecular mechanisms of post-lithium treatment against cerebral ischemic reperfusion (I/R) injury and associated cognitive deficits in rats. Methods : I/R injury was induced by right middle cerebral artery occlusion and lithium (40 and 60 mg/kg) were given intraperitoneally, 24 h after the insult and continued for 1 week with 24-h interval. Using Lasser Doppler, cerebral blood flow was monitored before, during and after MCAO induction. Besides behavioral, biochemical, and histological evaluation, levels of tumor necrosis factor alpha (TNF-α) and brain-derived neurotrophic factor (BDNF) were also estimated. Results : I/R injury resulted in significant elevation of neurological deficits, oxidative stress, neuroinflammation, and cognitive impairments. We found that lithium injection, 24 h after I/R-injury continued for 1 week, dose dependently prevented behavioral abnormality and cognitive impairments. Moreover, lithium attenuated the levels of oxidative stress and pro-inflammatory-cytokines TNF-α level. Further, lithium treatments significantly reduced neuronal damage and augmented healthy neuronal count and improved neuronal density in hippocampus. These neuroprotective effects of delayed lithium treatment were associated with upregulation of neurotrophic factor BDNF levels. Conclusion : Delayed lithium treatment provides neuroprotection against cerebral I/R injury and associated cognitive deficits by upregulating BDNF expression that opens a new avenue to treat I/R injury even after active cell death.